Happiness connects: The impact of mood on self-other integration - Zhang, Jing; Hommel, Bernhard (Frontiers in Psychology, 2022)
Converging evidence suggests a considerable plasticity of self-representation and self-other boundaries. But what are the factors controlling this plasticity? Here we explored how changes in an individual’s affective state impact his/her self-other representation. Participants watched short videos to elicit happiness or sadness before rating unfamiliar faces with happy or sad expressions. After watching the happy video, participants showed more self-other integration of happy than sad faces, while watching the sad video reduced integration for both happy and sad faces equally. This finding suggests the interaction of two processes: Positive mood biases metacontrol towards flexibility, which fosters the processing of features in which self and other might overlap, and possible overlap increases self-other integration. Negative mood, in turn, biases metacontrol towards persistence, which focuses processing on strictly task-relevant feature dimensions, so that possible overlap is less likely to have an impact.